Degradation profiles of biodegradable plastic films by biodegradable plastic-degrading enzymes from the yeast Pseudozyma antarctica and the fungus Paraphoma sp. B47-9. (July 2017) - Sato, Shun; Saika, Azusa; Shinozaki, Yukiko; Watanabe, Takashi; Suzuki, Ken; Sameshima-Yamashita, Yuka; Fukuoka, Tokuma; Habe, Hiroshi; Morita, Tomotake; Kitamoto, Hiroko
Abstract: Esterases from the yeast Pseudozyma antarctica (PaE) and the fungus Paraphoma sp. B47-9 (PCLE) can degrade biodegradable plastics (Shinozaki et al., 2013; Suzuki et al., 2014). The degradation profiles of plastic films composed of poly(butylene succinate), poly(butylene succinate- co -adipate), or poly(butylene adipate) by these enzymes were characterized by liquid chromatography-mass spectroscopy in terms of the molecular structures and molecular weights of the degradation products. Monomers and oligomers with molecular weights corresponding to dimers to octamers were identified as products of degradation by PaE in an aqueous reaction solution, irrespective of the type of biodegradable plastic film. Size-exclusion chromatography indicated that the number-average molecular weight of degraded films decreased with reaction time, suggesting that PaE degraded polyester films randomly into monomer units (endo-type degradation). PCLE also degraded polyester films randomly into monomer units, albeit more slowly than did PaE.